Use of purified soluble antigens of sheep pox-virus in serodiagnosis* - RAO, T V S; NEGI, B S; BANSAL, M P (The Indian Journal of Animal Sciences, 2013)
A soluble antigen fraction of sheep poxvirus was isolated by ultracentrifugation of the clarified scab suspension prepared from the pox lesions of experimentally infected sheep. The residual infectivity studies showed these soluble antigens to be noninfectious. They were subsequently purified by subtractive immuno-affinity chromatography to remove healthy skin proteins. The purified soluble antigen fraction and its antiserum were then evaluated for the diagnosis of sheep-pox by using various serological tests including agar-gel precipitation, counter immunoelectrophoresis, reverse phase passive haemagglutination and enzyme-linked immunosorbent assays. The utility of soluble antigens is discussed.